Diversion Against Crime by Children Confronting the Law to Achieve Restorative Justice - Zulita Anatasia (Fakultas Hukum Universitas Lampung, 2021)
The purpose of this writing is to try to find out the existence of law enforcement regarding diversion in the handling of cases committed by children in the Juvenile Justice System Law and to see the effectiveness of implementing the diversion policy in handling cases of criminal acts committed by children. The research was carried out in a normative juridical manner, with a statute approach and a conceptual approach using descriptive qualitative analysis. The results of this paper show that law enforcement regarding cases involving children with a diversion policy is rigidly regulated in Law, namely Law Number 11 of 2012 concerning the Juvenile Justice System, as well as related regulations such as Law Number 23 of 2002 concerning Child Protection, and Law -Law Number 13 of 2006 concerning Protection of Witnesses and Victims. In addition to law regulations there are implementing regulations such as Government Regulation Number 65 of 2015 concerning Guidelines for the Implementation of Diversion and Handling of Children Not Aged 12 (Twelve) Years Old and Supreme Court Regulation Number 4 of 2014 concerning Guidelines for Implementing Diversion in the Juvenile Criminal Justice System. In addition, the effectiveness of law enforcement does not run effectively in practice, this shows that the diversion policy to realize restorative justice is not being implemented properly, the linkages between external and internal components are not evenly distributed, both law enforcers and the roles of stakeholders, this has an impact The diversion policy and the goal of realizing restorative justice which has not been effectively implemented are influenced by several factors such as limited Human Resources (HR) who have not supported the implementation of the SPPA Law and training for legal structures.